Functional Analysis of the teosinte branched 1 Gene in the Tetraploid Switchgrass (Panicum virgatum L.) by CRISPR/Cas9-Directed Mutagenesis - Liu, Yang; Wang, Weiling; Yang, Bing; Currey, Christopher; Fei, Shui-zhang (Frontiers in Plant Science, 2020)
Tillering is an important biomass yield component trait in switchgrass (Panicum virgatum L.). Teosinte branched 1 (tb1)/Branched 1 (BRC1) gene is a known regulator for tillering/branching in several plant species; however, its role on tillering in switchgrass remains unknown. Here, we report physiological and molecular characterization of mutants created by CRISPR/Cas9. We successfully obtained non-chimeric Pvtb1a and Pvtb1b mutants from chimeric T0 mutants using nodal culture. The biallelic Pvtb1a-Pvtb1b mutant plants produced significantly more tillers and higher fresh weight biomass than the wild-type plants. The increased tiller number in the mutant plants resulted primarily from hastened outgrowth of lower axillary buds. Increased tillers were also observed in transgene-free T1 monoallelic mutants for either Pvtb1a-Pvtb1b or Pvtb1b gene alone, suggesting Pvtb1 genes act in a dosage-dependent manner. Transcriptome analysis showed 831 genes were differentially expressed in the Pvtb1a-Pvtb1b double knockdown mutant. Gene Ontology analysis revealed downregulation of Pvtb1 genes affected multiple biological processes, including transcription, flower development, cell differentiation, and stress/defense responses in edited plants. This study demonstrates that Pvtb1 genes play a pivotal role in tiller production as a negative regulator in switchgrass and provides opportunities for further research aiming to elucidate the molecular pathway regulating tillering in switchgrass.